2003
DOI: 10.1007/s00530-003-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical video content description and summarization using unified semantic and visual similarity

Abstract: Video is increasingly the medium of choice for a variety of communication channels, resulting primarily from increased levels of networked multimedia systems. One way to keep our heads above the video sea is to provide summaries in a more tractable format. Many existing approaches are limited to exploring important low-level feature related units for summarization. Unfortunately, the semantics, content and structure of the video do not correspond to low-level features directly, even with closed-captions, scene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Hsu et al [9] tracked four topics with visual duplicates and semantic concepts, and found that near-duplicates significantly improved the tracking performance. Zhu et al [35] presented a hierarchical video content description and summarization strategy supported by a joint textual and visual similarity. Zhai et al [31] linked news stories by combining keyframe matching and textual correlation.…”
Section: Multimedia Information Retrievalmentioning
confidence: 99%
“…Hsu et al [9] tracked four topics with visual duplicates and semantic concepts, and found that near-duplicates significantly improved the tracking performance. Zhu et al [35] presented a hierarchical video content description and summarization strategy supported by a joint textual and visual similarity. Zhai et al [31] linked news stories by combining keyframe matching and textual correlation.…”
Section: Multimedia Information Retrievalmentioning
confidence: 99%
“…An interesting example of hierarchical agglomerative clustering using a variant of the average-linkage criterion is the semi-automatic approach proposed in [21], whose final aim is to extract a hierarchical summary. In this work similarity between shots is defined on arbitrarily chosen key-frames in terms of HSV color histogram and texture features.…”
Section: Shot-based Clusteringmentioning
confidence: 99%
“…The two measures proposed in [21] are used for evaluating each layer of the preview. The first one measures the clustering precision P (answering the question "how accurate is this summary layer?")…”
Section: Evaluation Criterion and Performance Measuresmentioning
confidence: 99%
“…Duygulu et al [12] presented the technique to mine and track the repeated sequence of shots. A hierarchical video content description and summarization strategy was proposed in [40] with the support of a joint textual and visual similarity. Zhai et al [37] linked news stories by combining keyframe matching and textual correlation.…”
Section: Related Workmentioning
confidence: 99%